2003
DOI: 10.1161/01.cir.0000079173.84669.4f
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Lesion Morphology in Patients With Acute Myocardial Infarction

Abstract: Background-Elevated serum C-reactive protein (CRP) is of clinical significance in the management of acute coronary syndromes, but there have been few in vivo studies detailing the relation between lesion morphology and elevated CRP in the setting of acute myocardial infarction (AMI). In this study, we investigated the relation between lesion morphology as seen under preintervention intravascular ultrasound (IVUS) and CRP in the acute phase of AMI. Methods and Results-Our patient population comprised 90 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 37 publications
7
103
2
4
Order By: Relevance
“…Shamsuzzaman et al (24) reported that the CRP level was signifi cantly higher in patients with OSA in comparison with the control, and a regression analysis showed that CRP was independently associated with OSA. Sano et al (25) reported that hs-CRP was positively correlated with atherosclerotic plaque rupture and thrombosis in patients with MI. Panteghini et al (26) and BNP were negatively correlated with LVEF in nonage and three months later in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Shamsuzzaman et al (24) reported that the CRP level was signifi cantly higher in patients with OSA in comparison with the control, and a regression analysis showed that CRP was independently associated with OSA. Sano et al (25) reported that hs-CRP was positively correlated with atherosclerotic plaque rupture and thrombosis in patients with MI. Panteghini et al (26) and BNP were negatively correlated with LVEF in nonage and three months later in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…14,15) Previous some studies have demonstrated that CRP, an acute phase representative protein, is associated with various complications including cardiac events in AMI. 16,17) SAA, also an important acute phase inflammatory protein, has an expanded dynamic range with different kinetics compared with CRP and is reported to be a more sensitive indicator of inflammation in some noncardiovascular inflammatory conditions. 18) When in vivo inflammation occurs, synthesis of SAA, as well as CRP, in the liver is accelerated by inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] On the other hand, there is now increasing evidence that acute coronary syndrome (ACS) is an inflammatory condition. [9][10][11] It is likely that smoking induces inflammation, an atherogenic lipid profile, and a propensity to thrombosis, thereby promoting the development of coronary atherothrombosis. However, it is uncertain if chronic inflammation, which is provoked by smoking, plays an etiologic role in 'smoker's paradox'.…”
mentioning
confidence: 99%
“…Retrospective pathological studies of patients with coronary artery disease who died suddenly showed culprit lesion plaque rupture in Ϸ70% of patients. 1,2,12,13 IVUS studies have reported varying frequencies of infarct-related plaque rupture in AMI patients: 15.8% by Kotani et al, 7 37.5% by Rioufol et al, 6 37% by Fukuda et al, 8 and 55.6% by Sano et al 14 The time from symptom onset to IVUS imaging was Ͻ7 days, 7 Ͻ4 weeks, 6 Ͻ10 hours, 8 and Ͻ6 hours, 14 respectively. In the present study, plaque rupture was observed in 66% of AMI patients; the time from symptom onset to IVUS imaging was 1.4Ϯ1.9 days.…”
Section: Discussionmentioning
confidence: 99%